Limnologia de lagos de várzea do rio Madeira com ênfase na diversidade e produção secundária da comunidade zooplanctônica - Negreiros, Natalia Felix (Universidade Federal de São Carlos, 2014)
The study of diversity and productivity can contribute to understanding the functioning of Amazonian ecosystems as a whole and especially to the conservation of its aquatic biota, considered one of the richest in species on the planet. The present study aimed to analyze the course of three years the limnological characteristics of three floodplain lakes of the Madeira River in the area of influence of the Santo Antônio hydroelectric plant on the Madeira, in the region near to Porto Velho, Rondônia, with emphasis on the zooplankton community. Samples were quarterly covering the four major hydrological periods: low water, flood, high water and ebb over three years (2010-2013). Physical, chemical and biological variables of the lakes were collected and correlated with species composition, biomass and production of zooplankton. The zooplankton community was characterized by high species richness (195 taxa) and high degree of endemism for the group of Copepoda Calanoida. The results showed that the three lakes have eutrophic or mesotrophic characteristics. The highest values of density and biomass of zooplankton in the lake occurred Cujubim. The rotifers were numerically dominant, but the Copepoda dominated in biomass and secondary production in lakes Cuniã and San Miguel. There was little variability in secondary production of zooplankton, being slightly higher in the lake Cujubim with increased production of copepods and rotifers in this lake. The rainfall variation demarcated the occurrence of well-defined hydrological periods, directly affecting the hydrodynamics of this region, controlling population fluctuations of zooplankton, probably brought by the increased availability of resources on the Madeira River in the flood season, playing an important role in the organization of food webs, and how to link the transfer of matter and energy in food chains.
Keywords: Amazônia; Lagos de várzea; Diversidade biológica; Zooplâncton; Produção secundária; Amazon; Aquatic biodiversity; Floodplain lakes; Zooplankton; Secondary production; CIENCIAS BIOLOGICAS::ECOLOGIA